2007
DOI: 10.1097/01.brs.0000263407.25009.6e
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Ligamentum Flavum Hypertrophy Is Due to Accumulation of Inflammation-Related Scar Tissue

Abstract: Accumulation of fibrosis (scarring) causes hypertrophy of the ligamentum flavum. Inflammation-related gene expression is found in the ligamentum flavum. It might be possible to prevent the hypertrophy of ligamentum flavum with antiinflammatory drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
172
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(177 citation statements)
references
References 21 publications
(35 reference statements)
4
172
1
Order By: Relevance
“…12 In our study, there was an increase in expression of the metalloproteinases in both groups, with patients with disc herniation presenting a greater increase, compared with the stenosis of the lumbar canal group, adding the inflammatory factor to the biomechanical hypothesis of Soo and Kee-Young. 12 Saiyro et al 8 detected the presence of inflammatory cytokines, such as COX-2 and interleukin 1, 6, 8 and 15 in ligaments with and without increased thickness. They also demonstrated, in their article, that RNAm expression of these inflammatory cytokines occurs before the actual ligament hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 In our study, there was an increase in expression of the metalloproteinases in both groups, with patients with disc herniation presenting a greater increase, compared with the stenosis of the lumbar canal group, adding the inflammatory factor to the biomechanical hypothesis of Soo and Kee-Young. 12 Saiyro et al 8 detected the presence of inflammatory cytokines, such as COX-2 and interleukin 1, 6, 8 and 15 in ligaments with and without increased thickness. They also demonstrated, in their article, that RNAm expression of these inflammatory cytokines occurs before the actual ligament hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 During hypertrophy of the ligamentum flavum, there is reduction in the content of elastic fibers and an increase in collagen fibers, calcification, ossification and chondrometaplasia. [4][5][6] Sairyo et al 7,8 have shown a correlation between the hardening of the ligamentum flavum and the degree of fibrosis, resulting in repetitive inflammatory processes due to the mechanical stresses that the ligament suffers during the movements of the spine. Park and collaborators demonstrated that an increase in TGFb (transforming growth factor beta) expression, the protein that controls cell proliferation and acts in the early stages of oncogenesis, is related to hypertrophy of the ligamentum flavum.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated that TNFa and IL-b have inhibitory effects on elastin gene expression in lung fibroblasts. 8,14 Considering that inflammatory cytokines are frequently observed in degenerative discs and LF, 15,32,41 it could be inferred that TNFa and IL-b play roles in inflammatory ECM remodeling via both elastin degradation by inducing MMP-9 secretion and blocking elastin regeneration at the gene transcription level. Recent studies have identified that MMPs are related not only to ECM remodeling, but also angiogenesis and phagocytosis during inflammation, 26 and they regulate cellular functions and growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…21,25,31 Sairyo et al demonstrated that LF hypertrophy is associated with scarring from inflammatory reactions. 31,32 It is important to understand the roles and cascades of MMPs in human LF cells because theoretically MMPs could be potential treatment targets for spinal stenosis. Additional histochemical and genotypic in vivo studies on inflammatory cytokines and MMPs are warranted in order to better understand the role of MMP-9 in elastin degradation.…”
Section: 44mentioning
confidence: 99%
See 1 more Smart Citation